Growth and stabilization of silver nanoparticles on carbon dots and sensing application - Shen, Liming; Chen, Meiling; Hu, Linlin; Chen, Xuwei; Wang, Jianhua (Langmuir, 2013)
Carbon dots (C-dots) have been proven to show the capability for direct reduction of Ag(+) to elemental silver (Ag(0)) without additional reducing agent or external photoirradiation by incubating Ag(+) with C-dots for 5 min in a water bath at 50 °C. Silver nanoparticles (Ag-NPs) are simultaneously formed with an average size of 3.1 ± 1.5 nm and grew on carbon dots. This process involves the oxidation of amine or phenol hydroxyl groups on the aromatic ring of C-dots. Meanwhile C-dots protect and stabilize the Ag-NPs from aggregation in aqueous medium; that is, the Ag-NPs are stable at least for 45 days in aqueous medium. The formed Ag-NPs cause significant resonance light scattering (RLS), which correlates closely with the concentration of silver cation, and this facilitates quantitative detection of silver in aqueous medium.